Wavelet-based hemodynamic analyzing method in event-related fMRI with statistical processing - Imaeda, Sayaka; Kobashi, Syoji; Kitamura, Yuri T; Kondo, Katsuya; Hata, Yutaka; Yanagida, Toshio (International Congress series, 2004)
Investigating the shape and time to peak (hemodynamic response [HR] delay) of the HR introduces a new facet of research on human brain function. This paper proposes a novel method for analyzing event-related functional magnetic resonance images (ER-fMRI). The method is based on wavelet transform. The principal feature of the method is that it can detect an activation area and estimate the HRF simultaneously. To evaluate the proposed method, experiments were done on phantom data and human subjects. The results showed that the method could detect the activation area equivalent to and more than SPM99. Then, examination of variability of HR delay among the activation areas suggests that HR delay at the motor area is significantly faster than that at the visual area.